2021
DOI: 10.1007/s00267-021-01473-y
|View full text |Cite
|
Sign up to set email alerts
|

Critical Barriers to Environmental Management System Implementation in the Nigerian Construction Industry

Abstract: The impact of different hazardous substances of the construction industry being released to the environment is alarming. This constitutes an adverse effect on the quality of life of construction workers and the populace at large. To reduce this menace, Environmental Management System (EMS) was put in place. Meanwhile, the implementation of EMS in the Nigerian construction industry (NCI) is not certain. This study, therefore, investigated the barriers to EMS implementation in the NCI to group them into a smalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 76 publications
1
19
0
Order By: Relevance
“…Interestingly, previous study revealed three critical impediments to EMS implementation in the NCI, namely, "knowledge barrier", "process barrier" and "culture and management barrier" (Ojo et al, 2021). Therefore, to avert these barriers, this study revealed the complementary drivers (intellectual enhancement strategies, documentation and cultural strategies, and motivation and tracking strategies) that could enhance EMS implementation in the NCI.…”
Section: Motivation and Tracking Strategiesmentioning
confidence: 72%
See 3 more Smart Citations
“…Interestingly, previous study revealed three critical impediments to EMS implementation in the NCI, namely, "knowledge barrier", "process barrier" and "culture and management barrier" (Ojo et al, 2021). Therefore, to avert these barriers, this study revealed the complementary drivers (intellectual enhancement strategies, documentation and cultural strategies, and motivation and tracking strategies) that could enhance EMS implementation in the NCI.…”
Section: Motivation and Tracking Strategiesmentioning
confidence: 72%
“…Thus, the need to investigate the drivers of EMS implementation in the NCI becomes imperative. In a recent study (Ojo et al, 2021), the barriers to implementation of EMS in the NCI were investigated. Ojo et al (2021) further suggested that complementary drivers of EMS implementation in NCI should also be investigated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, in a situation where an organisation noticed that competitors have started exportation of goods and services; this could propel devising other sustainable methods in the production process. Therefore, training would help to ameliorate knowledge de ciencies which is a critical impediment to sustainability (Ojo et al, 2021).…”
Section: Organisational-related Drivermentioning
confidence: 99%